Aqueous solution synthesis of Na3SbS4–Na2WS4 superionic conductors. Issue 4 (6th January 2020) - Yubuchi, So; Ito, Akane; Masuzawa, Naoki; Sakuda, Atsushi; Hayashi, Akitoshi; Tatsumisago, Masahiro
Abstract : We report a facile synthetic protocol from aqueous solution for Na3 SbS4 -Na2 WS4 superionic conductors with sodium-ion conductivity of 4.28 mS cm −1 at 25 °C, which is the highest one in reported sulfide electrolytes prepared via liquid-phase methods. Abstract : We report a route for the synthesis of Na3 SbS4 –Na2 WS4 superionic conductors from aqueous solution. Na3 SbS4 –Na2 WS4 has the highest high sodium-ion conductivity (4.28 mS cm −1 at 25 °C) of reported sulfide-based solid electrolytes prepared via liquid-phase methods. The antimony in Na3 SbS4 is replaced by tungsten in a higher valence state, which is charge-compensated by sodium vacancies in the form Na3− x Sb1− x W x S4 . Introducing sodium vacancies while maintaining the 3D conduction pathways increases the pre-exponential factor in the Arrhenius plots of ionic conduction. The development of a facile synthetic protocol, as well as the high ionic conductivity and excellent chemical stability of Na3 SbS4 –Na2 WS4 in the presence of water, is a major step towards the realization of all-solid-state sodium batteries.